"Nous ne nous ennuyerons pas !": l’amistat entre els tres savis liturgistes R. Amiet, A. Olivar i M. S. Gros a través de la correspondència Amiet-Olivar = "Nous ne nous ennuyerons pas!". The friendship between the three liturgistic scholars R. Amiet, A. Olivar and M. S. Gros as seen through the Amiet-Olivar correspondence - Colet, Ignasi M. Fossas i (Miscel·lània litúrgica catalana, 2023)
In this study we present 12 letters and 1 postcard from Robert Amiet addressed to Father Alexandre Olivar, a monk of Montserrat, between 1981 and 1993. These documents reveal in a certain detail the friendship between these two liturgists and with Monsignor M. S. Gros.